Massive silicon utilization facilitated by a benthic‐pelagic coupled feedback sustains deep‐sea sponge aggregations. Issue 2 (28th September 2020) - Maldonado, Manuel; Beazley, Lindsay; López‐Acosta, María; Kenchington, Ellen; Casault, Benoit; Hanz, Ulrike; Mienis, Furu
Abstract: Biogeochemical cycling of silicon (Si), largely affected by biological drivers, is pivotal to the ecological functioning of the ocean. Most knowledge regarding biological utilization of Si derives from research on phototrophic organisms circumscribed to the photic ocean (i.e., diatoms). Utilization of Si in the aphotic ocean, where heterotrophic silicifiers become relevant Si users, remains poorly investigated. Here we quantify the flux rates and stocks characterizing Si cycling across dense aggregations of the hexactinellid sponge Vazella pourtalesii established in the aphotic zone of the central Scotian Shelf, Nova Scotia, Canada. Although individual rates of silicic acid consumption were low compared to other sponge species and diatoms, the large abundance of individuals (6.5 million) over the extension of these sponge grounds (2105 km 2 ) leads to massive annual silicic acid consumption, invested in producing their siliceous skeletons of biogenic silica. This sponge activity accumulates large biogenic silica stocks both in the living population and in the sediments. Skeletal pieces in sediment revealed that a good portion of biogenic silica deposited to the bottom after sponge death recycles as silicic acid before being permanently buried. This biogenic silica–silicic acid turnover, facilitated by an unconventional silicification pattern that favors delamination and dissolution of V. pourtalesii spicules, causes silicic acid enrichment at oceanographic dimensions in the bottom water of the central Scotian Shelf. Silicic acid efflux from the bottom sustains a feedback mechanism that fulfills sponge needs for silicic acid and facilitates the persistence of sponge aggregations in the long term.